2019
DOI: 10.1038/s41467-019-10649-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving the diagnostic yield of exome- sequencing by predicting gene–phenotype associations using large-scale gene expression analysis

Abstract: The diagnostic yield of exome and genome sequencing remains low (8–70%), due to incomplete knowledge on the genes that cause disease. To improve this, we use RNA-seq data from 31,499 samples to predict which genes cause specific disease phenotypes, and develop GeneNetwork Assisted Diagnostic Optimization (GADO). We show that this unbiased method, which does not rely upon specific knowledge on individual genes, is effective in both identifying previously unknown disease gene associations, and flagging genes tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 53 publications
1
90
0
Order By: Relevance
“…2A, B ). Moreover, by using Genenetwork 34 , we found that the lncRNAs RP3-395M20.9 , AC007278.2 and AC104820.2 may be involved in tumour necrosis factor (TNF) signalling, neutrophil degranulation and chemokine receptor signalling, respectively, implying a role for these uncharacterized lncRNAs in immune regulation in CeD.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2A, B ). Moreover, by using Genenetwork 34 , we found that the lncRNAs RP3-395M20.9 , AC007278.2 and AC104820.2 may be involved in tumour necrosis factor (TNF) signalling, neutrophil degranulation and chemokine receptor signalling, respectively, implying a role for these uncharacterized lncRNAs in immune regulation in CeD.…”
Section: Resultsmentioning
confidence: 99%
“…We sought to infer biological function using a guilt-by-association co-regulation approach to identify clusters of shared molecular function (see Methods). We identified co-regulated genes by correlating our prioritized gene list in 1,588 principal components that were identified from the co-expression of 31,499 RNA-seq samples across multiple tissues 34 (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations